Kinerja Perawat Ditinjau Dari Lingkungan Kerja Dan Karakteristik Individu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT This research was done by mean of a correlational descriptive design with cross section with an analytic quantitative non experimental and qualitatively. The purpose of this study was to determine and to identify the following point: I ) the relationship between work environment with nurse performance, 2). the relationship between nurse individual characteristic with nurse performance, 3). The relationship between work environment with nurse individual characteristic, and 4). the combination relationship between work environment and nurse individual characteristic with the performance of nurses. The subjects of this study were 80 nurses, who worked at ten wards in In-patient Department Banyumas Regency General Hospital, and 20 of nurses interviewed to obtain qualitative data. The instrument was self administrated questionaire beside the chief observes and in-depth interview. The results of this study showed that there were a significant relationship between work environment with nurse performance, a significant relationship between individual characteristic of education with nurse performance, a significant relationship between work environment with individual characteristic work duration, age, marital status, education, also there were a significant combination relationship between work environment and individual characteristics of nurse education with nurse performance. Among 8 dimensions of the work environment it was proved that providing focus had the most contribution score total (37) point from (45). The finding of this study would be useful policy making in increasing the ingredients requires for creating a high-performance climate.